PENGGUNAAN KELAMBU BERINSEKTISIDA PERMETHRIN DI DESA SELEMAN KECAMATAN TANJUNG AGUNG KABUPATEN MUARA ENIM SUMATERA SELATAN - Yahya, Yahya (Publikasi Penelitian Terapan dan Kebijakan, 2011)
The study was aimed to know community participation in the use of permethrin insecticidetreated nets which have been distributed to peoples since 2006. Observasional study conducted in Seleman village of Tanjung Agung, district of Muara Enim province of Soulth Sumatera. The research was carried out in April to November 2010, 70 respondents in this village was interviewed drawn by Simple Random Sampling Method. The result showed that most of people have nets which weredistributed in 2006 (82,9%). Only 32 respondent (45,7%) know about the goal of permethrin insecticidetreated nets distribution. The results showed that most of people owned bed nets are now a bed nets were distributed in 2006 (82.9%). Only 32 respondents (45.7%) who know the purpose of mosquito nets distributed, because most respondents have not get an explanation when nets were distributed (51.4%). There are many respondents who do not understand the difference between the permethrin insecticidetreated nets and the usual mosquito nets (57.1%). Although 95.52% used nets every day, but only54.29% who knows how to use. Generally, all family members used nets (58.20%). But only 65.7% respondents knowing how to wash nets, 78.26% of whom do not know how to wash nets. Most respondents nets drying in direct sunlight (76.09%). All respondents did not know about heating action nets (heat-assisted regeneration). Despite wearing a mosquito net, 65.72% of respondents also use anti-mosquito coils. To increase the society knowledge, they need explanation of the purpose of permethrin insecticide-treated nets distribution, how to use permethrin insecticide-treated nets, how to wash and who are the priorities of family to use permethrin insecticide-treated nets. In addition it should also be socialized about mosquito net heating (heat-assisted regeneration) in order to restored the effectiveness of the insecticide on the nets.